KEPRIBADIAN KONSELOR PADA KH. ABDULLAH TSABIT THAHAH DAN TEKNIK PERUBAHAN PERILAKU - Abdul Mubdik; Abd. Mughni (Fakultas Dakwah Universitas Ibrahimy, 2022)
At first the students were not all well-behaved, but they did not discriminate between one another, the sense of tolerance that existed in the students was very strong, and they respected each other. Of course, from the behavior of the students at the Assalam Islamic Boarding School, there is a figure who is a reflection for them, namely KH. Abdullah Tsabit Thahah he is the figure who plays the most role in guiding and changing the behavior of students at the Assalam Islamic Boarding School. This study discusses the counselor’s personality values at KH. Abdullah Tsabit Thahah in guiding the behavior of students at the Assalam Isla-mic Boarding School. The technique used by KH. Abdullah Thabit Thahah in Guiding Santri. The method used in this study uses qualitative research methods. The data sources that have been obtained and collected are then analyzed descriptively through the technique of writing scientific papers according to the standards set by Ibrahimy University. So that this research is proven to be valid. Based on the results of the study, obtained data explaining that the personality of KH. Abdullah Tsabit Thahah according to the personality that exists in a counselor in general, the techniques and methods he uses in guiding students according to theories so that the behavior of students gradually gets better. Thus, KH. Abdullah Thabit Thahah is a mature figure in personality. KH. Abdullah Tsabit Thahah is a character whose personality is like a counselor and the technique used by him in guiding the behavior of the students of Pondok Pesantren Assalam in accordance with the theory of behavior change in guidance and counseling.